دلالة الاستفهام في شعر أبي مسلم البهلاني = Iinterrogative meaning in the poems of Abu Muslim al-Bahlānī - Haji Ibrahim, Majdi; Hamd, Said (IIUM Press, International Islamic University Malaysia, 2020)
يعد الاستفهام من الأساليب النحوية والبلاغية المستخدمة بكثرة لدى الشعراء، فمن خلاله يكشف المستفهم عما يدور في نفسه ويطلب به قضاء حاجاته. من هذا المنطلق، يأتي هذا البحث ليتناول بالدراسة دلالة الاستفهام في ديوان الآثار الشعرية لأبي مسلم البهلاني من خلال تتبع أدوات الاستفهام في الأبواب الخمسة الأولى من الديوان، وهي: الإلهيات والقصائد الدينيّة، والمدائح النبوية، والقصائد الوطنية، وقصائد الحكم والمواعظ، والمراثي، ويهدف البحث إلى توضيح المقاصد التي يرمي إليها الشاعر من وراء استخدام أدوات الاستفهام، وبيان دلالاتها الحقيقيّة والمجازية وما ترمي إليه من معانٍ بيانية من تقرير وتعجب وتقريع وغيرها من المعاني مستهدياً بما قرره علماء اللغة في ذلك. وقد توصل البحث إلى أن الاستفهام يكثر في أغراض شعرية معينة ويقل في أغراض أخرى، وقد ظهر الاستفهام في الديوان بكثرة في القصائد الوطنية، والمراثي، وقل في المدائح النبوية، والحكم والمواعظ، وجاء بصورة معتدلة في الإلهيات والقصائد الدينية. ****************************************************************************** Interrogative words are part of the grammatical and rhetorical expressions that are widely used by poets to bring out their feelings and to achieve their purposes. This paper attempts to study the interrogative meaning in the Arabic anthology entitled “Al-āthār al-shiʽriyyah li Abī Muslim al-Bahlānī” (The poetic effects of Abu Muslim al-Bahlānī) by tracing the interrogative tools in the initial five chapters of the anthology namely: religious and godly poems, prophetic praises, and patriotic poems, poems containing wisdom and advice and odes. This is to explain the purposes intended by the poet by using such tools and explaining their true pragmatic as well as figurative meaning that consist of, among others, admission, exclamation, rebuking etc. that were pointed out by the language scholars. Among the conclusions of the study are that some interrogative method are widely used while others are seldom; many of which came up in patriotic poems, odes but seldomly found in prophetic praises, wisdom and advise while in the poems concerning God and religious matters, they are moderately used. ******************************************************************************** Kata-kata tanya adalah sebahagian daripada ayat-ayat tatabahasa dan retorika yang diguna secara meluas untuk menyatakan perasaan-perasaan mereka untuk mencapai tujuan-tujuan hidup mereka. Kajian ini bertujuan untuk mengkaji makna kata tanya dalam antologi syair berjudul “Al-āthār al-shiʽriyyah li Abī Muslim al-Bahlānī” (Kesan-kesan puitis syair Abu Muslim al-Bahlānī) dengan mengesan kata-kata tanya dalam lima fasal pertama antologi beliau iaitu: syair-syair keagamaan dan ketuhanan, pujian kepada Rasul, syair patriotik, syair hikmah dan nasihat dan syair ratapan. In iadalah untuk menjelaskan tujuan-tujuan yang dimaksudkan oleh penyair apabila menggunakan kata-kata tanya tersebut dan untuk menjelaskan maksud pragmatik juga perlambangan yang mengandungi, di antaranya, pengakuan, takjub, penghujahan dan lain-lain spertimana yang dijelaskan oleh cendiakawan bahasa. Di antara kesimpulan yang didapati kajian ialah: penggunaan sesetengah kata tanya adalah lebih kerap daripada yang lain. Kebanyakannya digunakan dalam syair patriotik, ratapan namun kurang digunakan dalam syair pujian kepada Rasul, syair hikmah dan nasihat dan di dalam syiar-syair ketuhanan ia digunakan secara sederhana.